(untitled) (Damascus University Journal of agriculture sciences, 2021)
This research aimed to compare of two propolis gathering traps with the traditional method of local honeybees Apis mellifera syriaca, in the Southern Region of Syria. The effect of many factors on propolis production was studied. Experiments were carried out in two locations in Al Sweida city, Syria; Daher Aljabal (location1), and Alkom (location2), during the period from June 2016 to November 2016. The effect of collection method on propolis production was studied, by using four treatments, modern collection method (commercial plastic sheets with slots 30x3 mm and plastic screen 20x5 mm), traditional collection method, and control. Also the effect of different locations and months of the year on the productivity of bee colony of propolis were studied. The results showed that the modern collection method aced on traditional collection method and the control in propolis collection. The location1 (Daher Aljaba) aced on the location2 (Alkom) in propolis collection. In relation to the effect of months on propolis collection, the most amount of propolis was in November. The interaction of the three previous factors showed that The hives of (location1x plastic sheets with slots 30x3mm x November) and (location1x plastic plastic screen 20x5mm x october) produced the highest amount of propolis collected with an average of 6.99 g/colony/month and 5.80 g/colony/month¸ respectively.